Domain Swap Approach Reveals the Critical Roles of Different Domains of SYMRK in Root Nodule Symbiosis in Lotus japonicus - Li, Hao; Chen, Mengxiao; Duan, Liujian; Zhang, Tingting; Cao, Yangrong; Zhang, Zhongming (Frontiers in Plant Science, 2018)
Symbiosis receptor kinase (SYMRK) is a cell membrane-localized protein kinase containing extracellular malectin-like domain (MLD) and leucine-rich repeat (LRR) domains, which is critically required for both root nodule symbiosis (RNS) and arbuscular mycorrhizal symbiosis (AMS). SYMRK is widely distributed in the genomes of different plant species; however, the contribution of different domains of SYMRK and its homologs from other plant species to RNS is largely unclear. In this study, SYMRK and its homologs from three typical plant species including Medicago truncatula (for both RNS and AMS), Oryza sativa (for AMS but not RNS), and Arabidopsis thaliana (for neither RNS or AMS) were investigated using domain swap approach in response to rhizobia in Lotus japonicus. Full-length SYMRK from rice and Medicago but not from Arabidopsis could complement Lotus symrk-409 mutant plants to contribute RNS. The chimeric protein with the extracellular domain (ED) of LjSYMRK and cytoplasmic domains (CD) of SYMRK from both Medicago and rice but not Arabidopsis could contribute to RNS in Lotus, suggesting that the CD of SYMRK is required for symbiotic signaling. The chimeric receptors containing the CD of LjSYMRK (SYMRKCD) and the EDs of MtDMI2 (MtDMI2ED), OsSYMRK (OsSYMRKED), AtSYMRK (AtSYMRKED), NFR1 (NFR1ED), and NFR5 (NFR5ED) could complement Lotus symrk-409 mutant plants to develop nodules. However, MtDMI2 could partially complement Lotus symrk-409 mutants to form both effective nodules and ineffective bumps, which is similar to the complementation results from MtDMI2ED-LjSYMRKCD and LjSYMRKGDLC in Lotus symrk-409 mutants, suggesting that ED of SYMRK has a very fine-tune regulation for RNS in Lotus. The deletion of either MLD or LRR on SYMRKGDLC (a mutant version of SYMRK with GDPC motif replaced by GDLC) could contribute to RNS when overexpressed in Lotus symrk-409 mutants, suggesting that MLD and LRR domains might work together to be involved in symbiotic signaling and the LRR domain might play a negative role in LjSYMRKGDLC-mediated RNS. By mutagenizing the conserved amino acids on LRR domain, five serine residues were found to be required for the function of LjSYMRKGDLC in RNS. These finding precisely refine the molecular mechanisms of SYMRK function in symbiotic signaling in L. japonicus.